Mediators of outcome in trauma-focused psychotherapy with youth: a systematic review - Protic, Sonja; Wittmann, Lutz; Taubner, Svenja; Conejo Cerón, Sonia; Ioannou, Yianna; Heinonen, Erkki; Saliba, Andrea; Moreno-Peral, Patricia; Volkert, Jana; Barkauskiene, Rasa; Schmidt, Stefanie Julia; Rangel Santos Henriques, Margarida Isabel; et al. (Trauma, violence & abuse, 2024)
This article aimed to provide a systematic narrative synthesis of existing studies on the mediators of change in psychotherapy with adolescents (10-19 years) and transition age youth (TAY) (20-29 years) who have experienced trauma-related symptoms or posttraumatic disorder. Additionally, we were interested in identifying psychotherapy-, trauma type-, and clients’ age- and gender-specific mediators of treatment outcome. Following the preferred reporting items for systematic reviews and meta-analyses, a total of 3,723 studies published in PubMed and PsycINFO databases were screened against inclusion criteria, revealing 15 eligible studies. No studies with only TAY were found; therefore, all results were limited to therapy with adolescents. Cognitive mediators were tested in 66% of selected studies, followed by parents/family-related, mental-health-related, therapy-related, and behavioral mediators. Moderate evidence was found for posttraumatic cognitions, whereas therapeutic alliance seemed to be a promising candidate for future research. Striking absence of non-cognitive-behavioral therapy interventions, emotional and adolescent-specific mediators, as well as studies with males and in non-Western societies was evident. Future original studies would benefit from applying methodological rigor in respect to mediation testing.
Gesehen am 05.02.2025